Ab initio исследование фосфоресценции гетеро[8]циркуленов; Известия вузов. Физика; Т. 62, № 3 (735) - Валиев Р. Р. Рашид Ринатович; Барышников Г. В. Глеб Владимирович; Черепанов В. Н. Виктор Николаевич; Сундхольм Д. Даге (2019, 2019)
Заглавие с экрана